The Influence of Project Based Learning Towards Students’ Speaking Skill (An Experimental Study in SMAN 2 Serang City) - Ika Handayani; Dimas Ghiffari (ENJEL: English Journal of Education and Literature, 2026)
The purpose of this study was to determine how project-based learning affected the speaking skills of eleventh-grade students at SMAN 2 Kota Serang-Banten. The researcher employed cluster random sampling as the sampling strategy and a quantitative approach with a real experimental design. According to the pre-test results, the experimental class's minimum score was 48, whereas the control class's minimal score was 32. The experimental class's highest score was 84, while the control class's highest score was 72. We can conclude that there was no significant difference between the two classes' pre-tests. The experimental class's minimal score on the post-test was 62, while the control class's minimum score was 60. The experimental class had a maximum score of 86, whereas the control class had a maximum score of 76. We can conclude that there was a significant difference between the two classes' pre-tests. T.count≥t_table, or 7.37 ≥ 2.00, was determined based on the outcome of the test of mean difference significant (independent t_test). The alternate theory was approved. At the eleventh grade of SMAN 2 Kota Serang, it can be concluded that project-based learning had an impact on students' speaking skills. It is suggested for the English teachers to apply the PjBL model and focus on making students be more active in speaking class.